The Effect of Product, Price Place, Promotion, People, Process and Procedure, also Physical Evidence to the Visits Decision of Tourism Place of Karanggongso Beach Trenggalek Regency - Mukhamad Aziz Taufiqi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
This research aims to know the effect of product, price, place, promotion, people, process and procedure, also physical evidence to the visits decision of tourism place of Karanggongso Beach Trenggalek Regency.The research type was explanatory research which explains causal relationship between variables through hypothesis testing. This research used sample for 100 respondents which taken from tourist population in Karanggongso Beach Trenggalek. The research was conducted in Karanggongso Beach on December 2015. Sample taking used purposive sampling technique. Test kit that used to test this research instrument was validation test, reliability test, and classical assumption test. Hypothesis test was conducted using F test and t test. Data analysis technique used multiple linear regression analysis.From the test result, it could be concluded that visits decision variable (Y) affected by product variable (X1) for 0.244; price (X2) for -0.190, place (X3) for 0.197, promotion (X4) for 0.154, people (X5) for 0.147, process and procedure (X6) for 0.168, also physical evidence (X7) for 0.237. In this research, it showed that the effect of product, price, place, promotion, people, process and procedure, also physical evidence was 68.7% to the tourist visits decision. Based on F test, it could be found that product, price, place, promotion, people, process and procedure, also physical evidence affected simultaneously to the visits decision. Based on t test, it could be found that product, price, place, promotion, people, process and procedure, also physical evidence affected partially to the visits decision, whereas product was dominantly affected to the tourist visits decision. Keywords: Tourism, Marketing Mix, Purchasing Decision